Orai1 Inhibitors as Potential Treatments for Pulmonary Arterial Hypertension. Issue 9 (27th September 2022) - Masson, Bastien; Le Ribeuz, Hélène; Sabourin, Jessica; Laubry, Loann; Woodhouse, Emily; Foster, Richard; Ruchon, Yann; Dutheil, Mary; Boët, Angèle; Ghigna, Maria-Rosa; De Montpreville, Vincent Thomas; Mercier, Olaf; et al.
Abstract : Background: Pulmonary arterial hypertension (PAH) is characterized by progressive distal pulmonary artery (PA) obstruction, leading to right ventricular hypertrophy and failure. Exacerbated intracellular calcium (Ca 2+ ) signaling contributes to abnormalities in PA smooth muscle cells (PASMCs), including aberrant proliferation, apoptosis resistance, exacerbated migration, and arterial contractility. Store-operated Ca 2+ entry is involved in Ca 2+ homeostasis in PASMCs, but its properties in PAH are unclear. Methods: Using a combination of Ca 2+ imaging, molecular biology, in vitro, ex vivo, and in vivo approaches, we investigated the roles of the Orai1 SOC channel in PA remodeling in PAH and determined the consequences of pharmacological Orai1 inhibition in vivo using experimental models of pulmonary hypertension (PH). Results: Store-operated Ca 2+ entry and Orai1 mRNA and protein were increased in human PASMCs (hPASMCs) from patients with PAH (PAH-hPASMCs). We found that MEK1/2 (mitogen-activated protein kinase kinase 1/2), NFAT (nuclear factor of activated T cells), and NFκB (nuclear factor-kappa B) contribute to the upregulation of Orai1 expression in PAH-hPASMCs. Using small interfering RNA (siRNA) and Orai1 inhibitors, we found that Orai1 inhibition reduced store-operated Ca 2+ entry, mitochondrial Ca 2+ uptake, aberrant proliferation, apoptosis resistance, migration, and excessive calcineurin activity in PAH-hPASMCs. Orai1 inhibitors reduced agonist-evoked constriction in human PAs. In experimental rat models of PH evoked by chronic hypoxia, monocrotaline, or Sugen/hypoxia, administration of Orai1 inhibitors (N-4-[3, 5-bis(Trifluoromethyl)-1H-pyrazol-1-yl]phenyl-4-methyl-1, 2, 3-thiadiazole-5-carboxamide [BTP2], 4-(2, 5-dimethoxyphenyl)-N-[(pyridin-4-yl)methyl]aniline [JPIII], or 5J4) protected against PH. Conclusions: In human PAH and experimental PH, Orai1 expression and activity are increased. Orai1 inhibition normalizes the PAH-hPASMCs phenotype and attenuates PH in rat models. These results suggest that Orai1 should be considered as a relevant therapeutic target for PAH.